A Surviving Herd of Endangered Wood Bison at Hook Lake, N.W.T.? - Van Camp, Jack (ARCTIC, 1989)
Bison in the Hook Lake area of the Northwest Territories (N.W.T.) are classified and managed as low value, diseased, plains bison (Bison bison bison) x wood bison (B.b. athabascae) hybrids. Their classification is founded on the hypothesis of universal hybridization in Wood Buffalo National Park (WBNP) and surrounding areas. This hypothesis is not supported by the confirmed samples of relatively pure wood bison taken from the range of the northern population WBNP in 1963 and 1965. . The probability of finding wood bison is greatest in the most remote and inaccessible Hook Lake area of the Slave River lowlands, where a small population survives after a prolonged population collapse. These animals may be at least partially descended from a relict population that predates WBNP. Historical, behavioural, morphometric, photographic and observational evidence is consistent with this hypothesis, but conclusive evidence from available taxonomic tests has not been collected. The current set of policy, legislation and international law empowers government to protect and manage the "endangered" wood bison but provides no protection for hybrids. Because of its current bio-political status, the Hook Lake herd is in imminent danger of extirpation from overharvesting, disease and overpredation or from deliberate depopulation to eradicate disease. If the Hook Lake bison are wood bison, the implications of a status change include: (1) the empowering of government to protect and manage the remaining herd; (2) the option to salvage and restore genetic diversity to the world population of wood bison; (3) alternatives that would greatly simplify future management strategies for free-roaming northern bison populations; and (4) a contribution to the international objective of removing the wood bison from danger of extinction.Key words: wildlife, bison, taxonomy, conservation Mots clés: faune, bison, taxonomie, conservation